Trend 2010 - 2012. Statistics Canada. CANSIM: Travel and Tourism - International Travel | Country: Canada | Province: Northwest Territories | Table: Air passenger traffic and flights | Variable: Domestic sector | Units: #, 2010-2012. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-200. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Travel and Tourism - International Travel | Country: Canada | Province: Northwest Territories | Table: Air passenger traffic and flights | Variable: Domestic sector | Units: #, 2010-2012. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-200. Dataset: Presents statistics on socioeconomic variables related to travel by foreigners in Canada and by Canadians outside Canada. Data include expenditures, port of entry and exit, country of origin and destination, main purpose of trip, trip duration, activities, and modes of transport used. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Industry, Business, and Commerce, International Relations and Trade Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Tourism, International Tourists, Travel Expenditures, International Tourism, Travel Industry, Tourism Industry